A Corner of White - Moriarty, Jaclyn (New York : Arthur A. Levine Books, 2013)
Fourteen-year-old Madeleine of Cambridge, England, struggling to cope with poverty and her mothers illness, and fifteen-year-old Elliot of the Kingdom of Cello in a parallel world where colors are villainous and his father is missing, begin exchanging notes through a crack between their worlds and find they can be of great help to each other.
Keywords: Interpersonal relations -- Fiction; Magic -- Fiction; Missing persons -- Fiction; Color -- Fiction; Princesses -- Fiction; Cambridge (England) -- Fiction; England -- Fiction